N-Methyl-D-Aspartate(NMDA) Receptor and Voltage-Gated Potassium Channel (VGKC) Antibody-Associated Encephalitides Presenting as First Episode Acute Psychosis - Tang, Charmaine; Tan, Kevin; Lim, Geraldine; Tan, Lynnette; Tay, Kay Yaw; Kandiah, Nagaendran; Abdin, Edimansyah; Verma, Swapna K. (Frontiers in Psychiatry, 2019)
Acute psychosis is not an uncommon presenting feature in immune-mediated encephalitides. Most patients improve if properly diagnosed and treated expediently with immunotherapy. Our study aimed to describe the frequency, clinical spectrum and long-term outcomes in patients presenting with acute psychosis who have anti-NMDA receptor or anti-VGKC encephalitis. We recruited patients aged 16-50 years presenting with <1 month of psychotic and neurological symptoms including cognitive dysfunction, seizures, abnormal movements and/or autonomic dysfunction. Between September 2011 and October 2013, 60 patients with first episode acute psychosis were screened; 15 were recruited and included for analyses. Four (26.7%) patients were diagnosed with anti-NMDA receptor encephalitis and 1 (6.7%) with anti-VGKC encephalitis. We found that the mean serum white blood cell (WBC) count (12.8 x 109/L ± 4.8 vs 7.9 x 109/L ±2.6; p = 0.05) and cerebrospinal fluid WBC count (106 cells/µL ± 101 vs 8.5 cells/µL ± 18.9; p = 0.05) were significantly higher in positive cases. Although not statistically significant, certain prodromal features such as fever, headache, confusion, facial dyskinesia and hypersalivation were more likely to be present in positive cases. Patients with autoimmune encephalitis also tended to be more unwell, with the majority requiring intensive care, had lower global assessment of functioning scores (30±10 vs 53.7±21.2, p=0.09), and were not well enough to complete standard psychiatric and cognitive assessments at presentation. Autoimmune encephalitis is not uncommon in patients with acute psychosis. Elevated WBC counts, certain prodromal features and a more severe illness at presentation should prompt appropriate evaluation.